Video Animasi Berbasis Budaya Lokal sebagai Media Inovatif dalam Peningkatan Mahārah Al-Kalām - Nevy Agustina; Koderi; Muslim, Ahmad Bukhari; Ghazi, Fachrul; Erlina (Shaut al Arabiyyah, 2025)
This study aims to develop and analyze the effectiveness of locally-based animated videos as an innovative medium for improving Arabic speaking skills (mahārah al-kalām) at the secondary school level. The background of this research is the low speaking ability of students due to the use of conventional and less contextual learning media. The integration of local cultural elements is expected to provide a more meaningful learning experience by linking Arabic to the social and cultural context of students. The research method used was a Systematic Literature Review (SLR) of various national and international studies published in the period 2019–2025 through the Scopus, ERIC, DOAJ, and Garuda databases. The analysis was conducted using a content analysis approach to examine the effectiveness of animated videos, the forms of local cultural integration, and their influence on student motivation and communication skills. The results of the study show that locally-based animated videos are effective in improving students’ fluency, accuracy, and confidence in speaking Arabic. Expert validation shows the suitability of content, appearance, and language, while student responses show an increase in interest and interaction. The integration of local culture also strengthens character and cultural appreciation. Thus, this media is effective and contextual in Arabic language learning in the digital age.